Pengaruh Servicescape, Emotional Satisfaction, Perceived Service Quality, Hospital Image Terhadap Patient Loyalty - Budiman, Michael; Riorini, Sri Vandayuli (SEIKO : Journal of Management & Business, 2023)
Patient loyalty dibutuhkan untuk mencegah pasien berpindah ke rumah sakit lain. Patient loyalty merupakan kunci keberhasilan tenaga kesehatan dan manajemen rumah sakit. Patient loyalty dapat membantu mengurangi pembelotan pasien, menghemat biaya untuk memperoleh pelanggan baru, dan mencegah penggunaan hadiah sebagai upaya menarik pelanggan.Penelitian ini dilakukan untuk menganalisis pengaruh servicescape, emotional satisfaction, perceived service quality, hospital image terhadap patient loyalty. Penelitian ini menggunakan data primer berupa kuesioner yang terdiri dari 33 pertanyaan yang dikumpulkan dari 224 responden yang menggunakan layanan Rumah Sakit Umum Kelas B milik swasta di Jakarta, pengambilan data dilakukan pada Mei 2023. Pengujian hipotesis dilakukan dengan structural equation modeling (SEM) dengan menggunakan aplikasi AMOS 21. Hasil penelitian menunjukkan bahwa servicescape berpengaruh positif terhadap emotional satisfaction. Servicescape berpengaruh positif terhadap perceived service quality. Emotional satisfaction berpengaruh positif terhadap hospital image. Perceived service quality berpengaruh positif terhadap hospital image. Hospital image berpengaruh positif terhadap patient loyalty. Penelitian ini dapat digunakan sebagai bahan pertimbangan bagi manajerial rumah sakit untuk merancang strategi mempertahankan dan meningkatkan kualitas layanan guna menciptakan hospital image dan patient loyalty. Kata Kunci: Servicescap; Emotional Satisfaction; Perceived Service Quality; Hospital Image; Patient Loyalty. Abstract Patient loyalty is needed to prevent patients from moving to other hospitals. Patient loyalty is the key to the success of health workers and hospital management. Patient loyalty can help reduce patient defections, save costs to acquire new customers, and prevent the use of gifts as an effort to attract customers. This research was conducted to analyze the effect of servicescape, emotional satisfaction, perceived service quality, hospital image on patient loyalty. This study uses primary data in the form of a questionnaire consisting of 33 questions collected from 224 respondents who use the services of privately owned Class B General Hospital in Jakarta. Data collection was carried out in May 2023. Hypothesis testing was carried out using a structural equation model (SEM) using an application AMOS 21. The results showed that servicescape has a positive effect on emotional satisfaction. Servicescape has a positive effect on the perception of service quality. Emotional satisfaction has a positive effect on the image of the hospital. Perceived service quality has a positive effect on the image of the hospital. Hospital image has a positive effect on patient loyalty. This research can be used as material for consideration for hospital managers to design strategies to maintain and improve service quality in order to create hospital image and patient loyalty. Key word: Servicescape; Emotional Satisfaction; Perceived Service Quality; Hospital Image; Patient Loyalty